A model of integrated lung and focused heart ultrasound as a new screening examination in infants at risk of respiratory or hemodynamic compromise - Yasser Elsayed; Mohamed Abdelmawla; Michael Narvey; Jens Wrogemann (Hygeia Press di Corridori Marinella, 2017)
Objective: This was a feasibility study to determine whether an educational program conducted over 2 days followed by 25 performed studies under supervision equips physicians with the skills to accurately interpret and perform integrated lung ultrasound (LUS) and focused heart ultrasound (FHUS) as a screening exam in infants at risk of respiratory or hemodynamic compromise. Methods: We conducted a training course over 2 days (total of 16 hours) to teach fellows how to interpret a pre-designed model of LUS and FHUS, as a screening exam for infants at risk of respiratory or hemodynamic compromise. Then trainees performed 25 cases with different neonatal lung and functional heart issues. The screening model included only the basic views required to evaluate common lung parenchymal and functional neonatal heart conditions in sick infants. The accuracy of interpretation during the course was assessed by Kappa. Results: The inter-rater agreement between all trainees and instructor improved on the second day of the course to Kappa 0.86 (95% CI: 0.72-0.97) for LUS views and 0.78 (95% CI: 0.69-0.91) for FHUS views. The inter-rater agreement between trainees themselves improved from Kappa 0.64 (95% CI: 0.47-0.81) for LUS on day one to 0.89 (95% CI: 0.81-0.96) on day two. And from 0.58 (95% CI: 0.44-0.73) on day one to 0.75 (95% CI: 0.68-0.84) on day two. Conclusion: Bedside screening, using integrated LUS and FHUS can be a useful adjunct to clinical examination in infants at risk of respiratory or hemodynamic compromise.